2018
DOI: 10.1158/1538-7445.am2018-3
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3: Metronomic chemotherapy with cyclophosphamide (Cy) and the repositioned drug losartan (Los) for the treatment of M-234p triple negative murine mammary adenocarcinoma

Abstract: Metronomic chemotherapy (MCT) refers to the chronic, equally spaced, delivery of low doses of chemotherapeutic drugs, without extended interruptions. Drug repositioning in oncology refers to the use of drugs formulated for other indications that showed antitumor potential. Los is an antagonist of angiotensin II receptor used to treat hypertension. We aim to study the combined effect of metronomic Cy+Los on M-234p tumor. Female BALB/c mice were orthotopically challenged with M-234p (day 0) and distributed, on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, we found that MCT with CY plus Losartan, an angiotensin II receptor antagonist, is a successful drug combination that, interestingly, caused % 60 of complete regressions in a very aggressive murine model of TNBC [54]. We also shed some light into the mechanisms The main characteristics of the mentioned investigations are summarized in Table 1.…”
Section: Pre-clinical Settingmentioning
confidence: 96%
“…Recently, we found that MCT with CY plus Losartan, an angiotensin II receptor antagonist, is a successful drug combination that, interestingly, caused % 60 of complete regressions in a very aggressive murine model of TNBC [54]. We also shed some light into the mechanisms The main characteristics of the mentioned investigations are summarized in Table 1.…”
Section: Pre-clinical Settingmentioning
confidence: 96%